Think better, you dumbass: Online hateful speech as epistemic violence - Morales, Esteban; Hodson, Jaigris; O’Meara, Victoria (AoIR Selected Papers of Internet Research, 2026)
Online violence and abuse pose significant challenges to public discourse, as it exacerbates existing power structures and marginalizes diverse epistemic perspectives. In this context, this study examines the epistemological consequences of hateful and toxic speech in online news comment sections, conceptualizing it as a form of epistemic violence—an effort to erase particular ways of thinking. Examining a dataset of toxic and hateful comments from The Conversation Canada, our findings emphasize four mechanisms of epistemic violence: insulting, labelling, ridiculing, and dehumanizing. These mechanisms function to delegitimize alternative epistemic positions and reinforce ideological conformity. Furthermore, these mechanisms disproportionately target those with marginalized identities along racial, gender, and political lines, further entrenching hegemonic power structures. Our research contributes to scholarship on digital epistemologies and platformized violence, highlighting the need for strategies that foster epistemic pluralism rather than simply suppressing toxic discourse.